1985
DOI: 10.21236/ada160517
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal versus Unimodal Information Processing of Words

Abstract: Sonarmen are constantly confronted with information presented simultaneously through different sensory modalities. Verbal information is one type of input to which they are exposed. Little is known regarding the effect of undirected attention when verbal information is presented siinultaneously to the auditory and visual modality. The question of interest is how do unimodal and nail timodal presentation conditions differentially affect, performance? FINDINGS The superiority of any particular modality depends u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…Kinchla (1974) referred to this effect as the redundant signals effect (RSE). The RSE has shown to be a rather robust phenomenon in work with simple stimuli, such as lights and tones (Loveless, Brebner, & Hamilton, 1970) and sonar detection (Halpern & Lantz, 1974;Lewandowski & Kobus, 1989), as well as with more complex stimuli, such as letters (Miller, 1982) and words (Lewandowski, Hursh, & Kobus, 1985;Lewandowski & Kobus, 1993). That is, subjects typically respond more accurately or quickly to redundant bimodal stimuli than to unimodal stimulus presentations.…”
Section: Advantages Of Bimodal Presentationmentioning
confidence: 99%
“…Kinchla (1974) referred to this effect as the redundant signals effect (RSE). The RSE has shown to be a rather robust phenomenon in work with simple stimuli, such as lights and tones (Loveless, Brebner, & Hamilton, 1970) and sonar detection (Halpern & Lantz, 1974;Lewandowski & Kobus, 1989), as well as with more complex stimuli, such as letters (Miller, 1982) and words (Lewandowski, Hursh, & Kobus, 1985;Lewandowski & Kobus, 1993). That is, subjects typically respond more accurately or quickly to redundant bimodal stimuli than to unimodal stimulus presentations.…”
Section: Advantages Of Bimodal Presentationmentioning
confidence: 99%
“…Studies which have compared single and dual-modality presentation conditions on sonar-like tasks have yielded mixed findings (1,(10)(11)(12)(13), although most investigators have concluded that a combined visual and auditory approach should be retained in sonar operation. Recently, Lewandowski and Kobus (14) found that detection threshold was lowered by more than 1.2dB to both visual and auditory targets when they were presented simultaneously rather than separately.…”
mentioning
confidence: 99%
“…Some suggest that a response to two redundant stimuli in two modalities is faster than a response to one stimulus in either modality (coactivation) (3,8). Others have stated that reaction time (RT) to redundant bimodal stimuli is shorter than RT to the slower single stimulus, but no shorter than RT to the faster single stimulus (12,15). It appears that the RT results are confounded by the inherent differences between auditory and visual processing time.…”
mentioning
confidence: 99%
“…For example, found that target detection thresholds were reduced when an equivalent sonar target was concurrently presented in both the visual and auditory channels. Lewandowski, Hursh, and Kobus (1985) extended this finding in an analogous task by presenting words to subjects in either visual or auditory channels, or in both channels.…”
Section: Introductionmentioning
confidence: 71%
“…Such results have been demonstrated using simple stimuli as lights and tones (Nickerson, 1973) as well as more complex stimuli as sonar signals (Kobus et al, 1986), letters (Miller, 1982), and words (Lewandowski, Hursh, & Kobus, 1985). A long-standing interest in the processing of dual signals has been evidenced by sonar operators and research scientists working with sonar systems.…”
Section: Introductionmentioning
confidence: 99%